PROVIDING OF FUNCTIONAL STABILITY OF MEASURING UNIT OF STABILIZATION AND ORIENTATION SATELLITE SYSTEM MOVEMENT PARAMETERS - Firsov, S. N. (Radio Electronics, Computer Science, Control, 2013)
The analytical tools for the number of the redundant measurers and their layout in the unit definition are suggested as a result of the research. The criteria, execution of which provides the functional stability in situation of a measurer’s single complete failure at the classical majority circuit level, are defined. Relatively to a single axis the majority circuit allows to counteract a single failure only. The failure is not classified as a fault or a defect. This fact does not enable to use the designed-in structure redundancy of the majority circuit in full measure. The disadvantage of the functionally stable measuring unit with a minimal structural redundancy usage is that such type of the device enables to counteract only a single complete failure, no matter which one of its measurers has failed. Its irrefutable advantage is that the usage of certain algorithms provides the counteraction of the sensitive elements’ multiple partial failures if the failures appear in no more than two sensitive elements. It is necessary to insert the additional structural redundancy in order to dispose the disadvantage of a single complete failure counteraction in the redundant measurer. The application of these tools makes possible to form the measurers’ redundant constructions, satisfying the signal and structural diagnosability criteria and enabling the opportunity to revitalize the measurements in contingency, caused by the kinds of the failures, in real time. The criteria, satisfaction of which provides the functional stability in conditions of the redundant measuring unit’s sensitive element single complete failure at the classical majority circuit level, are formed. The conditions providing the counteraction of the multiple partial and complete failures are formulated.